Monitoring Jaringan Internet Kantor Pusat Administrasi Universitas Muhammadiyah Palembang - Sayfudin (CV. Multi Kreasi Media, 2023)
The importance of the internet in everyday life makes human life inseparable from the internet but without realizing it, the use of the internet is sometimes used by irresponsible parties to steal data packets through data packet traffic on the internet using the sniifing method by utilizing open source software called wireshark, for that we need to understand that the use of the internet, especially those that still use the http protocol. When you want to access a website that still uses the http protocol, it is advisable not to use a public network, because in this study it has discussed that the http protocol can provide confidential data such as users and passwords, this happened in the administrative center office of the University of Muhammadiyah Palembang where after research there were several applications that still used the http protocol, of course this was dangerous for users. For this reason, this research has provided advice to UPT-IT as the responsible unit to immediately upgrade the protocol from http to https so that internet users can use the internet without fear of confidential data being stolen by irresponsible parties.